2018
DOI: 10.1002/jcp.27037
|View full text |Cite
|
Sign up to set email alerts
|

Irisin promotes cardiac progenitor cell‐induced myocardial repair and functional improvement in infarcted heart

Abstract: Irisin, a newly identified hormone and cardiokine, is critical for modulating body metabolism. New evidence indicates that irisin protects the heart against myocardial ischemic injury. However, whether irisin enhances cardiac progenitor cell (CPC)-induced cardiac repair remains unknown. This study examines the effect of irisin on CPC-induced cardiac repair when these cells are introduced into the infarcted myocardium. Nkx2.5 CPC stable cells were isolated from mouse embryonic stem cells. Nkx2.5 CPCs (0.5 × 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…In addition, irisin protects cardiomyocytes against hypoxia and reoxygenation injury and the heart against ischemiareperfusion (I/R) injury [7]. Irisin generated a protective effect against myocardial I/R injury by suppressing the opening of the mitochondrial permeability transition pore [8] through a SOD2dependent mitochondria mechanism [9]. The protective effects of irisin have also been found in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, irisin protects cardiomyocytes against hypoxia and reoxygenation injury and the heart against ischemiareperfusion (I/R) injury [7]. Irisin generated a protective effect against myocardial I/R injury by suppressing the opening of the mitochondrial permeability transition pore [8] through a SOD2dependent mitochondria mechanism [9]. The protective effects of irisin have also been found in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with recombinant irisin significantly increases phosphorylated p38 and phosphorylated ERK in both primary rat and 3T3-L1 adipocytes, while cotreatment with an inhibitor of either p38 or ERK or both abolishes the irisin-induced upregulation of UCP1 expression (Zhang et al, 2014). Irisin has been shown to promote Nkx2.5positive cardiac progenitor cell-induced cardiac regeneration, neovascularization and functional improvements in the ischemic heart (Zhao et al, 2019). Moreover, administration of irisin promotes the proliferation of human umbilical vein endothelial cells and cord formation via the ERK pathway (Wu et al, 2015), suggesting that irisin plays a role in guarding against cardiovascular diseases.…”
Section: Irisin Biogenesis and Biological Aspectsmentioning
confidence: 99%
“…Recently, irisin has been found to protect against the pathologic process of MI via its anti-apoptotic, pro-angiogenetic, and cardiac regenerative functions Liao et al, 2019;Zhao et al, 2019). showed that irisin treatment induced remarkable improvements in ventricular functional recovery and reduction of infarct size in the Langendorff perfused ischemia/reperfusion (I/R) injury heart of mice via suppressing the opening of mitochondrial permeability transition pore, which results in mitochondrial swelling, and protecting mitochondrial function to reduce cardiomyocyte apoptosis.…”
Section: Irisin and Fibroblast Growth Factor 21 (Fgf21)mentioning
confidence: 99%
“…Liao et al (2019) reported that treatment with irisin for 2 weeks significantly reduced infarct size and fibrosis in MI mice, significantly increased angiogenesis in the ischemic area, and decreased cardiomyocyte apoptosis via activating the ERK signaling pathway. Besides, it has been recently reported that irisin can induce cardiac regeneration and functional improvement of MI mice via promoting the function of cardiac progenitor cells (CPCs) (Zhao et al, 2019). Thus, irisin is a key exercise-induced cardioprotective factor exerting multiple functions in MI.…”
Section: Irisin and Fibroblast Growth Factor 21 (Fgf21)mentioning
confidence: 99%